"How can we make it work for you?" Enabling sporting assemblages for disabled young people. (November 2021) - Carroll, Penelope; Witten, Karen; Duff, Cameron
Abstract: Disabled young people have lower levels of participation in community life than nondisabled peers across a number of domains, including sporting activities, with profound implications for health, wellbeing and life course opportunities. Playing sport is a defining feature of identity for many young people in Aotearoa/New Zealand. Participation in sporting activities provides opportunities to develop competencies, to have fun and to compete, while also providing a sense of inclusion and peer group belonging. However, despite policies promoting inclusion of disabled young people in school and club sport, ableist attitudes and practices still function to exclude individuals who do not fit able-bodied norms. Drawing on recent 'assemblage thinking' in health and cultural geography, this paper explores the material, social and affective dimensions of 'enabling' and 'disabling' sporting assemblages, drawing on interviews with 35 disabled young people (12–25 years), parents and key informants. Many reported instances of demoralising exclusion in mainstream sporting activities. Some turned to adaptive sporting codes, designed for inclusion. In our exploration of participants' embodied experiences of enabling and disabling assemblages we employ assemblage theory to examine how social, affective and material forces and processes converge to either enable or constrain participation in local sporting activities. We close with a brief assessment of the implications of our analysis for ongoing efforts to promote inclusion for disabled youth in physical activity. Highlights: Disabled young people have lower sports participation levels than non-disabled peers. Ableist attitudes and practices frequently exclude those who do not fit able-bodied norms. Ableist attitudes produce social, cultural and physical barriers to participation. Disability-specific sports can enable experiences of pleasure, freedom and inclusion. Assemblage thinking has helped identify forces that enable/constrain participation.